0nce upon a time, Africa and China... - (:unkn) unknown (My University, 2011)
Préface à Julien Bokilo, China in Africa: Competition between China, traditional trade partners of Africa et BRIC countries,Paris, L'Harmattan, 2011
Keywords: African Research